THE LEVEL OF ACTIVITY IN THE IMPLEMENTATION OF LESSON STUDY - Khairul Izad Abd Rahman; Zuraidah Abdullah; Husaina Banu Kenayathulla, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The lesson study was introduced in Malaysia in 2008. Since 2011, lesson study become one of the strategies in professional learning communities in Malaysia. There are challenges in sustaining the implementation of lesson study in class, especially to help students to overcome difficulties in studying Additional Mathematics. The purpose of this study is to evaluate the level of activity on the implementation of lesson study for the subject Additional Mathematics based on the perceptions of 247 teachers, 247 school leaders, and 247 school experts using the purposive sampling method. Descriptive analysis was performed in this study. The findings of the study show that the evaluation of the activity level based on teachers’ perception was high where the mean score was 3.90. Similarly, the overall scores based on school leaders’ perceptions (Mean = 4.20) and school experts’ perceptions (Mean = 4.07) were also high. Thus, lesson study is seen to be able to improve professional skills and practices in the pursuit of quality results.